Comparative Research on The Application of Positioning Technology to Intelligent Clothing for Preventing Children from Getting Lost. Issue 1 (February 2021) - Shi, Wang; Qian, Wang; Ning, Zhang
Abstract: In view of the increasingly severe problem of lost children, application of emerging technologies to solve the problem has become a major concern in the society in the era of intelligence. In this paper, the application and development of the positioning technology system are analyzed by means of comparative research, so as to give reference to the application and development of positioning technology in future Intelligent clothing for preventing children from getting lost.